2016
DOI: 10.1093/infdis/jiw329
|View full text |Cite
|
Sign up to set email alerts
|

Desialylation ofNeisseria gonorrhoeaeLipooligosaccharide by Cervicovaginal Microbiome Sialidases: The Potential for Enhancing Infectivity in Men

Abstract: Previous studies have demonstrated that Neisseria gonorrhoeae sialylates the terminal N-acetyllactosamine present on its lipooligosaccharide (LOS) by acquiring CMP-N-acetyl-5-neuraminic acid upon entering human cells during infection. This renders the organism resistant to killing by complement in normal human serum. N-acetyllactosamine residues on LOS must be free of N-acetyl-5-neuraminc acid (Neu5Ac; also known as "sialic acid") in order for organisms to bind to and enter urethral epithelial cells during inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Consistent with this hypothesis, intra-urethral inoculation of male volunteers with 5000 CFU 'pre'-sialylated gonococci (strain MS11 mkC) infected only one of five (20%) of subjects, while inoculation of the same number of unsialylated bacteria infected five of six (86%) of individuals (Schneider et al 1996). Ketterer et al (2016) showed that cervical secretions obtained from women infected with gonorrhea contain sialidase in quantities sufficient to desialylate LOS, which may facilitate transmission of infection from women to men. Collectively, these data all support a key role for LOS sialylation in pathogenesis, thereby making it an attractive target for immunotherapeutic strategies to combat multidrug resistance.…”
Section: A Critical Role For Los Sialylation In Vivomentioning
confidence: 72%
See 2 more Smart Citations
“…Consistent with this hypothesis, intra-urethral inoculation of male volunteers with 5000 CFU 'pre'-sialylated gonococci (strain MS11 mkC) infected only one of five (20%) of subjects, while inoculation of the same number of unsialylated bacteria infected five of six (86%) of individuals (Schneider et al 1996). Ketterer et al (2016) showed that cervical secretions obtained from women infected with gonorrhea contain sialidase in quantities sufficient to desialylate LOS, which may facilitate transmission of infection from women to men. Collectively, these data all support a key role for LOS sialylation in pathogenesis, thereby making it an attractive target for immunotherapeutic strategies to combat multidrug resistance.…”
Section: A Critical Role For Los Sialylation In Vivomentioning
confidence: 72%
“…This may reduce FH * /Fc binding and subsequent complement activation, thereby compromising efficacy of the molecule. However, sialidase levels vary by as much as 89-fold across gonorrhea-infected women (Ketterer et al 2016); therefore, the extent of desialylation of N. gonorrhoeae can also be expected to vary widely. Sialic acid levels also vary in female genital secretions during different phases of the menstrual cycle (Iacobelli, Garcea and Angeloni 1971).…”
Section: Potential Limitations Of Fh * /Fcmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-standing interest has been how N. gonorrhoeae changes its surface structure to facilitate receptorspecific epithelial cell invasion during transmission between the sexes. We now have a possible scenario that answers this question, with the studies by Ketterer et al [7] reported in this issue of The Journal of Infectious Diseases. As described below, their findings are exciting in that they implicate sialidases provided by the cervicovaginal microbiome as facilitators of rendering N. gonorrhoeae more amenable to infection of the male urethra.…”
mentioning
confidence: 87%
“…The presence of cervical mucus or microscopic PMN counts ≥10 seen microscopically on an oil immersion field does not correlate well with gonococcal infection in the absence of co-infecting agents (18). Manifestations of gonococcal infection may be driven by environmental factors specifically associated with the genital tracts of men and women: these may include biofilm formation (19, 20); the influence of the microbiome, particularly in women (2125) and both direct and indirect molecular interactions between gonococci and specific host cells from men or women (2630).…”
Section: Introductionmentioning
confidence: 99%